Acute heart failure after liver transplantation: A narrative review. Issue 11 (7th October 2020) - Sharma, Sonal; Sonny, Abraham; Dalia, Adam A.; Karamchandani, Kunal
Abstract: Acute heart failure (AHF) is an under recognized yet potentially lethal complication after liver transplantation (LT) surgery. The increase in incidence of liver transplantation amongst high‐risk patients and the leniency in the criteria for transplantation, predisposes these patients to postoperative AHF and the antecedent morbidity and mortality. The inability of conventional preoperative cardiovascular testing to accurately identify patients at risk for post‐LT AHF poses a considerable challenge to clinicians caring for these patients. Even if high‐risk patients are identified, there is considerable ambiguity in the candidacy for transplantation as well as optimization strategies that could potentially prevent the development of AHF in the postoperative period. The intraoperative and postoperative management of patients who develop AHF is also challenging and requires a well‐coordinated multidisciplinary approach. The use of mechanical circulatory support in patients with refractory heart failure has the potential to improve outcomes but its use in this complex patient population can be associated with significant complications and requires a stringent risk‐benefit analysis on a case‐by‐case basis.